Islam dan Negara: Perdebatan dalam Pembuatan Perda Syariat di Kota Tasikmalaya - MA’MUN MUROD AL-BARBASY (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2016)
This paper discusses the debates behind the formulation of Sharia regulation in Tasikmalaya. This paper argues that the initiators of Sharia regulation in Tasikmalaya are coming from mainstream islamic organizations such as Muhammadiyah, Nahdlatul Ulama or Persis, but social organizations or non- mainstream islamic groups, such as Hizb ut-Tahrir Indonesia (HTI), Front de- fenders of Islam (FPI) and Laskar Thaliban, including PKPPSI and the Indone- sian Ulema Council (MUI). This debate is seen in the perspective of the relation- ship between Islam and the state. There are at least four important topics exam- ined in this paper: the linkages between Shariah regulation and islamophobia, resistance and acceptance of Sharia regulation, the relationship between notion of Shariah and political party ideology, and Sharia regulation as a product of democracy. This paper also agues that two largest Muslim organizations, Muhammadiyah and Nahdlatul Ulama, both in position as jam’iyah and jamaah, less contributed to the debate of Shariah regulation in Tasikmalaya.